PENGGUNAAN MEDIA SIG DENGAN APLIKASI QGIS TERHADAP HASIL BELAJAR SISWA KELAS X SMAN 1 BONTI - Muliadi Mikael; Sri Buwono; Ludovicus Maditya Hari Christanto (Universitas Tanjungpura, 2020)
AbstractThe research aims to analyse the influence of geographic information system media usage with the QGIS application in geography learning of the X-grade student learning outcomes at SMAN 1 Bonti. The research method used is the experimental method with the research form Quaisy own twith design nonequivalent control group design. The population of this study was all grade X students of SMAN 1 Bonti which amounted to 101 students. The sampling technique used is Simple Random Sampling. The data collection techniques in this study are measuring techniques. Based on the calculation of the study results of the control class and the experiment class obtained 4.581 and with ? = 5% and DK = 66 is 1.699, thus, Ha accepted. So, there is an influence on the use of geographic information system media with QGIS application in geography learning of grade X student learning outcomes at SMAN 1 Bonti. Based on the result of Effect Size calculation, effect size is 1.008 (high criteria). This means that the use of media media information system with the QGIS application can have a high influence on the student learning outcomes in class X SMAN 1 Bonti.Keywords: Geographic Information Systems Media, Learning Outcomes, QGIS Applications